2019
DOI: 10.1007/s00343-019-8196-8
|View full text |Cite
|
Sign up to set email alerts
|

Phycocyanin attenuates X-ray-induced pulmonary inflammation via the TLR2-MyD88-NF-κB signaling pathway

Abstract: Phycocyanin (PC), a natural algal protein, is reported for having anti-oxidant and antiinfl ammatory properties. We investigated its ability to attenuate lung infl ammation in mice subjected to X-ray radiation. Male C57BL/6 mice were assigned to the control, total body irradiation, PC pretreatment, and PC treatment groups. Mice in the PC pretreatment group were gavaged with 200 mg/kg PC for 7 consecutive days before irradiation, and those in the PC treatment group were gavaged with 200 mg/kg PC for 7 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Phycocyanin has been well documented to exert antiinflammatory effects by inhibiting NF-κB activation in a variety of animal and cellular models of inflammation. [39][40][41] In the present study, PCB showed an equivalent potency to phycocyanin against NF-κB activation and downstream inflammatory responses in human intestine and RAW264.7 cells (Fig. 6, 7b and d), suggesting the critical structural role of PCB in phycocyanin's anti-inflammatory activity.…”
Section: Discussionsupporting
confidence: 58%
“…Phycocyanin has been well documented to exert antiinflammatory effects by inhibiting NF-κB activation in a variety of animal and cellular models of inflammation. [39][40][41] In the present study, PCB showed an equivalent potency to phycocyanin against NF-κB activation and downstream inflammatory responses in human intestine and RAW264.7 cells (Fig. 6, 7b and d), suggesting the critical structural role of PCB in phycocyanin's anti-inflammatory activity.…”
Section: Discussionsupporting
confidence: 58%
“…Analogously, PC supplementation boosts antioxidant enzyme levels in the liver and alleviates hepatic oxidative stress due to its radical scavenging, lipid peroxidation prevention [35], and mitochondrial respiratory complex protective activity [36]. The anti-inflammatory ability of PC may stem from its inhibitory action on activating programmed cell death five protein (PCDP5)/nuclear factor κ-B or tool-like receptor 2/NF-κ-B pathways [37,38].…”
Section: Discussionmentioning
confidence: 99%